Analisis Penyebab Tingginya Food Costs dan Strategi Pengendalian Biaya Makanan pada Food and Beverage Product Department di Four Points Hotel by Sheraton Bali - Made Artajaya; I Gusti Agung Febrianto; Made Wahyu Chikara Wijaya (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2023)
Abstract The hotel's second largest revenue is food and beverage revenue. Four Points by Sheraton Bali Ungasan benefit from the sale of food and beverages, the income can be achieved maximally if the control of food cost effectively and efficiently. The objective of this study was to determine the cause of the high food cost at Four Points by Sheraton Bali Ungasan in 2020 and to determine the food cost control strategy by the food and beverage product department. Based on the percentage comparison between standard food costs and actual food costs period January - December 2020, there is a difference of 4.03%. This study uses a qualitative descriptive analysis technique of triangulation of sources using the theory of Dittmer, Ojugo, and Wiyasha. The results of this study indicated the purchasing section was not applied standard purchase specifications and standard prices. The receiving section did not check the quality and quantity of food from suppliers. Foodstuff storage did not apply FIFO and the storage space did not mind the feasibility and temperature. The issuing section did not apply storeroom requisition. The kitchen section did not apply the standard yield, standard recipe and standard portion size optimally, this causes high food costs. Keywords: Food Cost, Procurement of Foodstuffs, Control of Food Cost. Pendapatan terbesar kedua hotel adalah pendapatan makanan dan minuman. Four Points by Sheraton Bali Ungasan memperoleh keuntungan dari hasil penjualan makanan dan minuman, pendapatan yang dihasilkan dapat tercapai dengan maksimal apabila pengendalian bahan makanan dilakukan secara efektif dan efisien. Tujuan penelitian ini adalah untuk mengetahui penyebab tingginya food cost di Four Points by Sheraton Bali Ungasan pada tahun 2020 dan mengetahui strategi pengendalian food cost oleh food and beverage product department. Berdasarkan data persentase perbandingan antara standard food cost dan actual food cost periode Januari - Desember 2020, menunjukkan terdapat selisih sebesar 4,03%.